Ferdinand Braun, a life of the Nobel prizewinner and inventor of the cathode-ray oscilloscope - Kurylo, Friedrich (MIT Press, 1981)
This scientific biography, however, does considerably more than restore Braun to his proper reputation: it has a fascinating story to tell. Of particular interest is its account of the early days of radio transmission, and the competition of Braun and his associates with Marconi and company to extend the range and improve the reception of radio signals. The technical basis of Braun's contributions are clearly explained.